Dendrometer measurements of Mediterranean-alpine dwarf shrubs and micro-environmental drivers of plant growth – Dataset from long-term alpine ecosystem research in the Sierra Nevada, Spain (LTAER-ES) - Löffler, Jörg; Albrecht, Eike Corina; Dobbert, Svenja; Pape, Roland; Wundram, Dirk (ERDKUNDE, 2022)
Here, we present measurement data of stem diameter variability of three common woody plants, monitored in the Mediterranean-alpine biome for six consecutive years (2015–2020). These focal species (Astragalus granatensis, Cytisus galianoi, and Genista versicolor) are abundant across the Sierra Nevada mountain chain (Southern Spain) and will potentially be affected by severe future climatic changes predicted for the region, including increased aridification in a warming environment. Understanding their fine-scale radial growth-patterns in relation to local environmental parameters might gain further insights into future vegetational shifts. We therefore used 139 high-resolution dendrometers to continuously monitor specimens along a steep elevational gradient and at varying topographical positions within the heterogeneous topography of the region. Additionally, we measured on-site environmental conditions at each studied site, including soil moisture and soil temperature within the root zone. All data were recorded at hourly resolution and are presented as daily mean values. The dataset was collected as a part of our long-term alpine ecosystem research program (LTAER), which functions as the basis for our recent projects on the use of dendrometer data to better understand the physiological mechanisms and the environmental drivers of the ongoing alpine greening.